Cultural values Integration in English Language Learning for Indonesian Young Learners - Dewi, Nita Sari Narulita (Script Journal: Journal of Linguistic and English Teaching, 2017)
This study investigates cultural values Integration in English language learning for primary school level. A case study is chosen to explore the phenomenon of what aspects reflecting cultural integration in English language learning classroom and its impact on the learnersâ language learning. Data are gathered through observation and interview. The acquired data are analyzed using Thematic Analysis by Braun and Clarke (2006). The study reveals that in L1 and L2 culture based materials are designed to be transferred in the process, mostly listening skill, vocabulary and grammar are presented by the learners, strategy of teaching and learning are performed by the teacher and learners, and cultural awareness and nationalism reflection show their identity as Indonesian young learners.Keywords: Culture, English Language Learning, and Indonesian Young Learners